(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
The present study aimed to investigate the effects of exposure to a protocol of chronic mild stress (CMS) on the maintenance of a previously learned operant discrimination. Four experimentally naive male Wistar rats were subjected to 10 sessions of discriminative training (multiple VI 15 s / Extinction), 28 sessions of discriminative training concomitantly with exposure to CMS, and five sessions of discriminative training after the exposure to stress protocol. As a result, the discriminative indexes decreased, and the frequency of responses increased in the first two weeks of exposure to the stress protocol. In the last two weeks of exposure to the stress protocol, these effects reversed for most subjects. The frequency of reinforcement was maintained relatively constant throughout the study. When the CMS was interrupted, the discriminative indexes were superior to that observed in the baseline for most subjects. The results suggest that the first weeks of exposure to stress protocol can impair the discriminative control previously established.